Characteristics of Indonesian Teaching Materials for Foreign Speakers for the Business Communication Purposes - Juwanda Juwanda; Ida Zulaeha; Hari Bakti Mardikantoro; Tommi Yuniawan (International Conference on Science, Education, and Technology, 2023)
Indonesian language learning for foreign speakers (BIPA) has various objectives, one of them is BIPA learning for business communication purposes. For this reason, it is needed the special teaching materials for BIPA learners for business communication purposes. This research is to find out how the characteristics of BIPA teaching materials for business communication purposes. The method of the research is using qualitative method. The subject of the research is BIPA learners for business communication purposes which have 10 learners from various countries and different work backgrounds. The data of the research is in the form of questionnaire results of BIPA teaching materials needs for business communication purposes filled by BIPA learners for business communication purposes. The conclusion of the research results that the characteristics of BIPA teaching materials for business communication purposes as follows, (1) Characteristics of BIPA teaching materials for business communication purposes must be oriented to the needs of BIPA learners for business communication purposes, (2) contain business / work content, oriented to the ability of learners, (3) contain material as a whole which is arranged in an organized manner, (4) contain audio visuals, and (3) an easily accessible application.